Risk Factors of Coronary Artery Disease: A Hospital-Based Study - Devkota, Surya; Dhungana, Raja Ram; Pandey, Achyut Raj; Poudel, Chandra Mani; Shrestha, Hemant; Bhattarai, Anil (Journal of Nepal Health Research Council, 2022)
Background: Coronary artery disease is among the leading cause of morbidity and mortality worldwide. There are limited scientific evidence on the risk factors for coronary artery disease specific to the Nepalese context. This study aimed to determine the association of various modifiable cardiovascular risk factors with coronary artery disease in Nepal.Methods: It is a hospital-based case-control study conducted among 300 participants. Case group comprised of 150 newly diagnosed coronary artery disease patients attending Manmohan Cardiothoracic Vascular and Transplant Centre while the Age and sex matched non-cardiac patients (n=150) from the outpatient department of the Department of General Practice and Emergency Medicine of Tribhuvan University Teaching Hospital were recruited as controls. Adjusted odds ratios (AOR) were calculated using multivariable logistic regression. Results: Of the 300 participants, 208 (69.3%) were males and 92 (30.7%) were females. The mean age was 59.8 years ± 11 years (standard deviation). In multivariable analysis, current smoking (AOR=3.05, 95% CI: 1.61-5.78), hypertension (AOR=1.82, 95% CI: 1.08-3.09), diabetes (AOR=3.78, 95% CI: 1.91-7.47), family history of coronary artery disease (AOR=2.92, 95% CI: 1.27-6.71), and low high density lipoprotein (AOR= 2.0, 95% CI: 1.17-3.42) were significantly associated with coronary artery disease. Current alcohol use (AOR=0.51, 95% CI: 0.29-0.89) was identified as a protective factor for coronary artery disease.Conclusions: Among the modifiable cardiovascular risk factors, smoking, hypertension, diabetes, and low level of high density lipoprotein were significantly associated with coronary artery disease, which should be considered while developing public health interventions for cardiovascular disease prevention in Nepal in future.Keywords: Cardiovascular disease; coronary artery disease; Nepal